2018
DOI: 10.1186/s12870-018-1330-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation at qHd1 affects heading date acceleration at high temperatures with pleiotropism for yield traits in rice

Abstract: BackgroundRice is highly sensitive to temperature fluctuations. Recently, the frequent occurrence of high temperature stress has heavily influenced rice production. Proper heading date in specific environmental conditions could ensure high grain yield. Rice heading greatly depends on the accurate measurement of environmental changes, particularly in day length and temperature. In contrary to the detailed understanding of the photoperiod pathway, little has been known about how temperature regulates the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Temperature is also considered as a major environmental factor in plant flowering although the clear genetic factors have not been demonstrated yet in rice. Recently, the day-length independent flowering QTL, qHd1 encoding OsMADS51 showed reduced heading date in response to increased temperature (Chen et al, 2018). A large insertion (∼9.5 kb) at the first intron of OsMADS51 significantly reduced gene expression and caused tolerance to high temperature-induced flowering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is also considered as a major environmental factor in plant flowering although the clear genetic factors have not been demonstrated yet in rice. Recently, the day-length independent flowering QTL, qHd1 encoding OsMADS51 showed reduced heading date in response to increased temperature (Chen et al, 2018). A large insertion (∼9.5 kb) at the first intron of OsMADS51 significantly reduced gene expression and caused tolerance to high temperature-induced flowering.…”
Section: Resultsmentioning
confidence: 99%
“…Another upstream gene of Ehd1, OsMADS51 , is a flowering activator in SD with major effect and in LD with minor effect (Kim et al, 2007). Recent study by Chen et al (2018) identified that OsMADS51 is also involved in high temperature-induced flowering of rice. Oryza sativa Pseudo-Response Regulator 37 ( OsPRR37 )/ Hd2 also known as Ghd7.1 (Liu et al, 2013) functions as a flowering suppressor in both SD and LD conditions independently of Hd1 and Ehd1 pathways (Koo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They inferred that the difference was caused by the temperature difference from flowering to ripening between the two sub-populations, which was higher for the late-maturing sub-population. Similarly, a stronger effect of OsMADS56/qHd1 on grain weight was found to be associated with a higher air temperature (Chen et al, 2018). The average air temperature from flowering to ripening was 23.5C for G10-3 and G10-4, and 27.2C for G11-3 and G11-4.…”
Section: Discussionmentioning
confidence: 77%
“…Flowering time is closely related to the grain yield for crop, owing to its key role in maintaining an appropriate balance between full use of resources and avoidance of environmental stresses. Many heading date (HD) genes were reported to affect yield traits, and their natural variations have been used in rice breeding, such as Ghd7 [10], DTH8 / Ghd8 [11,12], Hd1 [13,14], OsPRR37 / Ghd7.1 / DTH7 / Hd2 [15,16,17], RFT1 [18] and OsMADS51 [19,20]. Abiotic stresses during flowering, such as high temperature, low temperature, and drought, can pose a serious threat to spikelet fertility and consequently induce yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between HD gene and abiotic stress has been given attention in recent years. The Ehd1 - Hd3a / RFT1 pathway responses stress signals mediated by Ghd7 [21], OsABF [22] or OsMADS51 [20]. They integrate low temperature, high temperature, and drought signals, respectively, into HD pathway, which induce or repress floral transition to avoid flowering in the stress environments.…”
Section: Introductionmentioning
confidence: 99%